Individual differences in the calibration of trust in automation - Pop, Vlad Liviu (Georgia Institute of Technology, 2013)
A large body of research has identified that one of the major factors influencing decisions about automation use is operator's trust. Studies have shown that operator trust can be affected by individual differences in expectancy. The purpose of this study was to investigate whether operators with an expectancy that automation is trustworthy are better at calibrating their trust to changes in the capabilities of the automation. We also investigated why this individual difference affects calibration. In a baggage screening task 176 participants searched for weapons in 200 x-ray images of luggage. Participants were assisted by an automated decision aid exhibiting different levels of reliability. Measures of expectancy that automation is trustworthy were used in conjunction with subjective measures of trust and of perceived reliability to identify individual differences in trust calibration. We found that operators with high expectancy that automation is trustworthy were more sensitive to changes (both increases and decreases) in automation reliability, and that this difference was caused by attributing errors to the situation rather than the automation.